The Correlation Between Perfectionism and Serum Thyroid Hormone Levels in Obsessive-Compulsive Personality Disorder Patients - Yildiz, Sevler; Kazgan, Asli; Tabara, Muhammed Fatih; Kurt, Osman; Atmaca, Murad (Aves, 2021)
Objective: Perfectionism is one of the leading clinical symptoms of the obsessive-compulsive personality disorder (OCPD). This research aimed to compare perfectionism and serum thyroid hormone levels between individuals with OCPD and healthy individuals of a control group. Methods: The serum levels of free T4, free T3, and thyroid-stimulating hormone of 37 patients diagnosed with OCPD and 36 healthy controls with similar sociodemographic traits were measured. Furthermore, the Sociodemographic and Clinical Data Form, the Beck Anxiety Inventory (BAI), the Beck Depression Inventory (BDI), and the Frost Multidimensional Perfectionism Scale (FMPS) were applied to all participants in the study. Results: There was a statistically remarkable correlation between the FMPS total score and the T3 level (r = -0.47, P =.004), and between the BAI and the T3 level (r = -0.41, P =.011). Conclusion: The research findings demonstrated that there could be a correlation between perfectionism and thyroid hormone levels.
Keywords: Obsessive-compulsive disorder; personality disorders; thyroid hormones; perfectionism